Nestabilna brazgotina kot kronična rana in možnost nastanka Marjolinovega ulkusa - Emeršič, Luka (Zdravniški vestnik, 2020)
Marjolin ulcer is a rare, highly aggressive type of squamous cell carcinoma. It emerges from chro - nic wound after a burn. Our goal was to point out the danger of malignant transformation of an unstable scar as a chronic wound (Marjolin ulcer) and possible options of treatment in our hospital and other hospitals in the world. At the University Medical Centre Ljubljana, Clinical De - partment of Plastic, Reconstructive, Aesthetic Surgery and Burns in the last 13 years we operated on 5 patients due to an unstable burn scar manifested as a chronic wound. We reviewed English literature on the topic of ulceration of the unstable chronic scar. Marjolin ulcer is a preventable epithelioma alteration. Every large wound that is left for secon - dary healing has a potential to develop into a chronic wound that can ulcerate and change into a malignant lesion. This is most often seen in burns and scars. If chronic wound has developed, biopsy and treatment are needed. Treatment was most effective when done as soon as possible and when there was no malignant alteration of the wound.
Keywords: burn; opeklina; rana; ulcer; ulkus; wound